Who is in favor of immigration - Gil S. Epstein; Shirit Katav-Herz (Bar-Ilan University, Department of Economics, 2019)
Population ageing affects most countries, especially developed ones. The elderly have increased in number as a result of increased longevity and a parallel decline in fertility. This phenomenon is placing an increasing burden on the young to finance intergenerational transfers to the old, which is creating a threat to the stability of the pension system and the long-run viability of society as a whole. One possible solution is to permit more immigration, which will both increase the labor force and broaden the tax base. Increasing immigration has a variety of effects on the local population, which vary according to age and wealth. One of these is the threat to local social norms and culture since immigrants tend to maintain the culture of their country of origin. This effect increases with the number of immigrants and reduces the attractiveness of immigration as a solution to population ageing. This paper examines immigration as a solution to the problem of ageing population, while considering the implication of immigration on social norms.
Keywords: J11; J15; J61; 330; Immigration; Social norms; Population ageing; Intergenerational transfers; Attitude toward immigrants